Navigating the New Normal: Discussing Electronic Music Scores During COVID-19 - Deck, Trevor; Madill, Kevin; McMillan, Brian (CAML Review / Revue de l'ACBM, 2024)
An edited transcript of a roundtable presentation held on Thursday, June 9, 2022, at the Canadian Association of Music Libraries (CAML) 2022 virtual conference. Through a series of six questions chosen to fit in a one-hour format, Music Librarians from three Canadian Universities discussed their experiences with the acquisition of e-score databases. Topics include motivation for acquisition, selection criteria, marketing strategies, patron responses, resource issues, and impact on print collections. This article is offered to a broad audience of library professionals in the belief that topics discussed will be applicable to collection development in subject areas apart from music.